Pengaruh Pemberian Pupuk NPK Phonska dan Pupuk Biourine Sapi Terhadap Pertumbuhan Bibit Pisang Rutai (Musa sp). - Kardiansyah Kardiansyah; Purwati Purwati; Iin Arsensi (Universitas Widya Gama Mahakam, 2017)
The Influence of Fertilizer NPK Phonska and Biourine Cow Fertilizer on the Growth of Banana Seeds of Rutai (Moses sp). The purpose of this study was to determine the effect of NPK Phonska and Biourine Cow Fertilizer on the Growth of Banana Seeds of Rutai. This study was conducted for 3 months, ie from September to December 2014. Research Campus Widya Gama Mahakam Samarinda. This research was arranged in Randomized Block Design (RAK) with 3 x 3 Experiment with 3 replications. The first factor is the provision of NPK Phonska (P) Fertilizer consisting of 3 levels, namely: po (control), p1 (50 grams of Phonska NPK fertilizer / plant), p2 (Provision of 100 grams of Phonska NPK fertilizer / plant). While the second factor is the provision of Biourine Cow Fertilizer (U) consisting of 3 levels, namely: u0 (Control), u1 (Giving 10 ml of Biourine Fertilizer / Plant), and u2 (Giving 15 ml of Biourine Fertilizer / Cow). The result showed that fertilizer NPK Phonska with dose of 100 g / plant / polybag (p2) can increase the growth of rutai banana seedlings where the highest growth parameters were 16 and 20 weeks after planting 15.89 cm and 21.25 cm, Then the parameter of increase of diameter is at 16 weeks after planting is 5,50 cm, and for parameter increase of leaf amount is at 16,20 and 24 weeks after planting that is 1,89 strands, 2,11 strands and 2,22 strands. Giving of Biourine Fertilizer Cow with dosage of 15 ml / liter of water / polybag (u2) can increase the growth of rutai banana seedlings where the highest highest plant growth parameters are at 16, and 20 weeks after planting ie 16.67 cm and 22.28 cm, then The parameter of diameter increase is 16 weeks after planting is 63,50cm, and for parameter increase of leaf number is at 16, and 24 weeks after planting that is 1,89 strands and 2,22 strands. The interaction treatment between NPK Phonska and Biourine Sapi fertilizer between 100 grams of NPK Phonska and Biourine Sapi 15 ml / liter of water / plant (p2u2) can increase the growth of rutai banana plants, where the parameters of plant height increase is 16, 20 weeks after planting 19,67 cm and 30,20 cm, then at parameter of diameter increase is at 16 weeks after planting that is 4,59cm, and on parameter of increase of leaf number is at 16, 20 and 24 weeks after planting that is 5,14 strands, 2, 67 strands and 3,00 strands. Keywords: NPK Phonska, Biourine Cow Fertilizer and Banana Rutai